Estudo do impacto das variáveis externas sobre as eleições dos prefeitos no Estado do Ceará utilizando o modelo de probabilidade Logit - Costa Junior, Argentino Jacinto da (2018)
The present study aimed to examine how the re-election of municipal managers affects performance of municipal management, through the external control variables (partisan ideology, per capita income, municipal and regional characterization HDI), If the probability of municipalities present irregularities in their performances. To this end, we sought to determine the impact on re-election of municipal mayors, in function of the probability of occurrence of irregularities in the provision of municipal accounts of the State of Ceará, explaining them based on Logit Probability model.